Trace.space: a psychogeographical community project with members of an arts and health organisation. Issue 1 (2nd January 2017) - Bridger, Alexander J.; Emmanouil, Sophia; Lawthom, Rebecca
ABSTRACT: In this article we present a psychogeographical community project involving members of an arts and health organisation. Using creative ways to improve the mental health and well-being of individuals, we draw on the concepts of trace and spaces to map relationships between researchers and participants. This project was underpinned by three aims which were: to do community group work to produce contributions both in and beyond the University; to playfully critique everyday life in consumer capitalist society and finally, to consider the extent to which personal and social changes could be enabled. To realise those aims, we put into practice a range of architectural, community psychological and psychogeographical methods such as photo-elicitation, dice walking and scavenger hunting. We also facilitated participatory workshops which involved the production of artistic maps, writing poems and short stories. We conclude the paper with reflections from stakeholders with conclusions and future psychogeographical research being considered.